Processamento a vácuo e armazenamento de doce misto dietético e funcional de frutas do cerrado - Brandão, Telma Melo (2015)
This work was carried out aimed to monitor the effect of temperature and storage time on chemical, physical and microbiological characteristics in the sweet mixed dietary and functional of cerrado fruits. Different formulations previously were developed of sweets mixed with pulps from cerrado fruits as: marolo, sweet passion fruit, soursop, murici and genipap, the sweet samples were previously submitted to sensory evaluation in order to reach the best formulation of sweet mixed. After sensory testing results the sweet mixed formulation chosen was the one that had in its composition pulps: marolo, sweet passion fruit and soursop plus other ingredients: polydextrose, fructo-oligosaccharide, carrageenan gum, locust bean gum, pectin of low methoxyl content, citric acid and potassium sorbate, sucralose, acesulfame-K. Polydextrose and fructo-oligosaccharide additions in the concentrations used become functional. The development steps were as follows: (1) in this study to evaluate chemical, physical, physico-chemical, microbiological and centesimal of fruit pulp (marolo, sweet passion fruit and soursop) used in the formulation as well the sweet mixed characterization at time zero. (2) To evaluate chemical, physico-chemical and microbiological analysis in sweet mixed stored for 180 days in BODs at temperatures 25°C and 35°C, in order to verify the changes that occurred in the sweet mixed compared to the pulp mixture of fruit in natura. (3) To evaluate the physical changes (water activity, color, texture’s profile and syneresis) during storage at both temperatures. As for the results: (1) pulp mixture had higher moisture, ether extract, acidity, bioactive compounds (carotenoids, vitamin C, total phenolic and antioxidant activity - DPPH) compared to sweet. The developed formulation showed good total dietary fiber content 43.37%, while the soluble fiber and insoluble fiber presented content 30.57% and 11.80%, respectively. (2) There was a significant effect of storage time for pH, soluble solids, titratable acidity, total carotenoids, total soluble sugars, total phenolics. Vitamin C and antioxidant activity showed interaction effect (temperature x storage time). Filamentous fungi and yeasts were not detected in sweet mixed during storage. (3) The sweet mixed dietary and functional from cerrado fruits stored at 35°C showed higher hardness, gumminess and chewiness, did not change the color characteristics.